Serum concentrations and tissue expression of a novel endocrine regulator fibroblast growth factor-21 in patients with type 2 diabetes and obesity - Mraz, M; Bartlova, M; Lacinova, Z; Michalsky, D; Kasalicky, M; Haluzikova, D; Matoulek, M; Dostalova, I; Humenanska, V; Haluzik, M (Clinical endocrinology, 2009)
OBJECTIVE: Fibroblast growth factor-21 (FGF21) is a novel endocrine and paracrine regulator of metabolic homeostasis. The aim of our study was to measure its serum concentrations in patients with obesity, obesity and type 2 diabetes mellitus (T2DM) and healthy subjects (C), and to assess the changes of its circulating levels and mRNA expression after dietary and pharmacological interventions. DESIGN: We measured biochemical parameters, serum FGF21, adiponectin, leptin and insulin levels by commercial ELISA and RIA kits, and mRNA expression in the liver, subcutaneous and visceral fat by RT PCR in 26 obese patients, 11 T2DM patients and 32 control subjects. The interventions were acute hyperinsulinaemia during isoglycaemic-hyperinsulinaemic clamp, very low calorie diet (VLCD) and 3 months treatment with PPAR-alpha agonist fenofibrate. RESULTS: Baseline serum FGF21 levels were significantly higher in both obese and T2DM patients relative to healthy controls. FGF21 levels in obesity did not significantly differ from T2DM group. Both 3 weeks of VLCD and 3 months of fenofibrate treatment significantly increased FGF21 levels. FGF21 mRNA expression in visceral fat was twofold higher in obesity relative to C group, while it did not differ in subcutaneous fat. VLCD significantly increased FGF21 mRNA expression in subcutaneous fat of obesity. 3-h hyperinsulinaemia during the clamp increased FGF21 levels in T2DM but not in C group. CONCLUSION: An increase in FGF21 levels after VLCD and fenofibrate treatment may contribute to positive metabolic effect of these interventions and suggests the possibility of direct positive metabolic effects of FGF21 in humans.
Keywords: leptin; Liver; játra; Obesity; fenofibrát; adiponektin; Adiponectin; Middle Aged; Diabetes Mellitus, Type 2; studie případů a kontrol; Leptin; Adult; diabetes mellitus 2. typu; Fenofibrate; ženské pohlaví; Gene Expression; Humans; fibroblastové růstové faktory; lidé středního věku; obezita; Fibroblast Growth Factors; exprese genu; dospělí; Female; lidé; Case-Control Studies